Adherence to Self-Regulation Systems in Electronic Commerce: Evaluations from the Perspective of Information Society Service Providers - López Jiménez, David (2011)
Internet constitutes a communication and distribution channel with a high level of social introduction. In any case, there is still a certain feeling of distrust towards internet, specially as a means of recruitment. To end this impression, self-regulatory systems were devised, in order to regulate all matters related to electronic commerce in depth, establishing the best legal and ethical practices, and ensuring full protection to the user. Aware of the benefits that, in practice, they hold, providers of the information society have chosen, considerating the aim of achieving full user confidence, to adhere to them. Spain is one of the countries of the European Union where, curiously, more self-regulatory systems coexist. Taking into account such particularity, we have performed a comprehensive empirical study, formulating various issues of interest to the added companies, with which we could learn different considerations from the perspective of such agents, for this new and suggestivequestion.